Investigating the alleviation of endothelial injury by apelin: insights from network pharmacology and in vitro experiments: Apelin alleviates the endothelial injury - Li, Yingbang; Yang, Yanfang; Xian, Caihui; Liang, Guowu; Bai, Yunpeng; Zhong, Hui; Zaixiang Zeng; Huang, Wendong (Cellular and Molecular Biology, 2025)
Vascular lesion is the most important complication of diabetes, and vascular endothelial injury is the basis of vascular lesions. Although apelin was considered to have a positive effect on cardiovascular, the potential mechanisms remain unclear. In this work, we aimed to determine whether apelin alleviates endothelial injury through Src/Stat3 pathway. In virtue of network pharmacology, Src/Stat3 was sifted of 44 overlapping targets of diabetes and apelin. Human umbilical vein endothelial cells (HUVECs) were treated with high glucose (HG) and oleic acid (OA) to simulate the physiological environment of endothelial injury in vitro. Cell viability and migration were promoted while apoptosis rate and lactic dehydrogenase (LDH) release were reduced in the presence of apelin. Not only the protein expression of phosphorylated Src and Stat but also eNOS were raised by apelin. In conclusion, apelin dramatically improved cell status by activating Src/Stat3 pathway and increasing expression of eNOS. Apelin may provide an opportunity for the development of cardiovascular drugs.